Some operational properties of the Laguerre transform - Rodrigues, M. M. (2018)
This paper is devoted to the study of some properties of the Laguerre transform. We define new properties of the Laguerre transform in a weighted $L_2-$space. Moreover, we present some results concerning the action of this integral transform over some class of polynomials.